ANALISIS PENDAPATAN PETANI KELAPA SAWIT DI DESA LUBOK BUAT - Aria; Setiawan, Rusdy; Hatta, Djuanda; Masniah, Andi (Ekonomi Pembangunan Fakultas Ekonomi, 2024)
This study aims to analyze the income of oil palm farmers in Lubok Buat Village, Sembakung Atulai District, Nunukan Regency. This research is a quantitative approach using a sample method, namely purposive sampling. The data in this study used primary data from 30 samples with data analysis using the net profit analysis method from the sale of production after deducting the total costs incurred. From the results of the study obtained the average total revenue is Rp. 2,205,814.- / Ha / Monthly or amounting to Rp. 26,469,767, - / Ha / Year with the average total production costs incurred is Rp. 596,556, -/Ha/Bln or amounting to Rp. 7,158,680,-/Ha/Th. So that the average net income of farmers after deducting the total cost of production is Rp. 1,609,257, - / Ha / Monthly or Rp. 19,311,087, - Ha / Year